Enhancing Employee Performance Within the Digital Workplace is a Key Focus - Fu, Chandra Kurniawan; Moeins, Anoesyirwan; Zami, Alex (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
In order to understand the purpose of this study, we will examine the utilization of information and its application. The study conducted at the West Java Provincial Education Office focuses on the impact of technology competence on employee performance. It also investigates the effects of information technology application on employee performance. Both factors, technology competence and the application of information technology, are analyzed both together and separately. To conduct this study, we employed two research methods: descriptive survey and explanatory survey. Our research specifically targeted the employees of the Education Office in West Java Province, with a sample size of 50 individuals as our focus of analysis. Our investigation aimed to explore the cause-and-effect relationship, while our time frame was cross-sectional in nature. Upon analyzing the study's findings, it was determined that the employees at the West Java Provincial Education Office exhibited a satisfactory level of application of information technology. Furthermore, the competencies of these employees were considered appropriate and sufficient for meeting their job requirements. Additionally, their workplace performance was discovered to be exceptionally outstanding. Moreover, it was observed that the combined impact of Information and Competence Technology has a significant effect on employee performance at the West Java Provincial Education Office. However, it is important to note that when considering individual factors, the influence of Information Technology on employee performance surpasses that of competence. As the integration of Information Technology has emerged as a dominant force in driving productivity, it should be prioritized in the endeavor to improve employee performance. Therefore, it is recommended that the West Java Provincial Education Office implement a suitable Information Technology Application by enhancing the user-friendliness of other information technology resources, enabling employees to carry out their duties with a higher level of professionalism